Probiotics for the prevention of surgical necrotising enterocolitis: systematic review and meta-analysis. Issue 1 (1st November 2017) - Rees, Clare M; Hall, Nigel J; Fleming, Paul; Eaton, Simon
Abstract : Aim of the study: Probiotic administration to preterm infants has the potential to prevent necrotising enterocolitis (NEC). Data from randomised controlled trials (RCT) are conflicting but meta-analyses seem to support this intervention. To date, these analyses have not focused on surgical NEC. We aimed to determine the effect of probiotic administration to preterm infants on prevention of surgical NEC. Methods: A systematic review of RCTs of probiotic administration to preterm infants was performed. Studies were included if RCT outcomes included any of (1) Bell's stage 3 NEC; (2) surgery for NEC; and (3) deaths attributable to NEC. Article selection and data extraction were performed independently by two authors; conflicts were adjudicated by a third author. Data were meta-analysed using Review Manager V.5.3. A random effects model was decided on a priori because of the heterogeneity of study design; data are risk ratio (RR) with 95% CI. Main results: Thirty-five RCTs reported NEC as an outcome. Seventeen reported surgical NEC; all RCTs were included. A variety of probiotic products was administered across studies. Description of surgical NEC in most studies was poor. Only 6/16 specifically reported incidence of surgery for NEC, 12/17 Bell's stage 3 and 13/17 NEC-associated mortality. Although there was a trend towards probiotic administration reducing stage 3 NEC, this was not significant (RR 0.74 (0.52–1.05), p=0.09). There was no effect of probiotics on the RR of surgery for NEC (RR 0.84 (0.56–1.25), p=0.38). Probiotics did, however, reduce the risk of NEC-associated mortality (RR 0.56 (0.34–0.93), p=0.03). Conclusion: Despite 35 RCTs on probiotic prevention of NEC, evidence for prevention of surgical NEC is not strong, partly due to poor reporting. In studies included in this meta-analysis, probiotic administration was associated with a reduction in NEC-related mortality.